2020
DOI: 10.1016/j.fertnstert.2020.08.1362
|View full text |Cite
|
Sign up to set email alerts
|

Fallopian Tube Endometriosis in Women Undergoing Operative Video Laparoscopy and Its Clinical Implications

Abstract: Post-abortion hysteroscopy: a method for early diagnosis of congenital and acquired intrauterine causes of abortions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Masson et al reported that the prevalence of tubal EM was 0.29%, 14 while Qi et al reported that the prevalence was 37.37% 9 . McGuinness et al 5 reported that the macroscopic incidence of tubal EM was approximately 12%, while the microscopic incidence of tubal EM was as high as 42.5%. Clement et al 10 found that approximately 25% of cases with tubal EM were in the interstitial mucosa, while 10% of cases were in the isthmic or ampullary mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Masson et al reported that the prevalence of tubal EM was 0.29%, 14 while Qi et al reported that the prevalence was 37.37% 9 . McGuinness et al 5 reported that the macroscopic incidence of tubal EM was approximately 12%, while the microscopic incidence of tubal EM was as high as 42.5%. Clement et al 10 found that approximately 25% of cases with tubal EM were in the interstitial mucosa, while 10% of cases were in the isthmic or ampullary mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of tubal EM has previously been reported to range from 4% to 11%, but these studies have been based on a macroscopic diagnosis 2–4 . Recent studies have reported a prevalence of tubal EM at 42.5%, based on pathological diagnosis, suggesting that the actual incidence of tubal EM may be underestimated 5 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent publication by McGuinness et al (1) regarding the incidence of fallopian tube endometriosis explores an issue relating to women with endometriosis that is not well investigated: what is the true incidence of both macroscopic and microscopic endometriotic lesions in the fallopian tubes of women undergoing minimally invasive surgery (MIS)? We are used to reading reports regarding the incidence of ovarian endometriosis or pelvic and even extrapelvic endometriosis.…”
mentioning
confidence: 99%